Supervision of Elementary School Teachers in Preparing Lesson Plan - Jonis Jonis (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2021)
The objectives to be achieved in this study are to find out how the supervision of elementary school teachers in preparing a lesson plan. Then to investigate how a teacher prepared the lesson plan in terms of several aspects such as the competence of a teacher in pedagogy, professional, personality and social. The method in this study was descriptive because this method makes it easier for researchers to express the symptoms that occur when conducting research. The form of research used in this study was a survey. The sample in this study were all teachers at Elementary School (SD) 01 Matang Suri, Indonesia totalling nine teachers consisting of four civil servants and five non-permanent teachers. Based on the results of data analysis, 270 (75%) questionnaire items were answered yes, and 90 (25%) were answered no with meaning that when the teacher was supervised, it was in a good category.